2013
DOI: 10.1002/mus.23797
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bifid median nerves and persistent median arteries and their association with carpal tunnel syndrome in a sample of latino poultry processors and other manual workers

Abstract: Introduction The prevalence of bifid median nerves and persistent median arteries, their co-occurrence, and their relationship to carpal tunnel syndrome (CTS) are only understood partially. Methods We screened 1026 wrists of 513 Latino manual laborers in North Carolina for bifid median nerves and persistent median arteries using electrodiagnosis and ultrasound. Results A total of 8.6% of wrists had a bifid median nerve, and 3.7% of wrists had a persistent median artery independent of subgroup ethnicity, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 20 publications
4
51
0
4
Order By: Relevance
“…The prevalence of bifid median nerves has been described previously in surgical, MR, and ultrasound studies . Our study showed that the occurrence of bifid median nerve is equal in patients with CTS (15.8%) and controls (18.5%).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The prevalence of bifid median nerves has been described previously in surgical, MR, and ultrasound studies . Our study showed that the occurrence of bifid median nerve is equal in patients with CTS (15.8%) and controls (18.5%).…”
Section: Discussionsupporting
confidence: 79%
“…The reported frequency of bifid median nerves varies from 0.8% to 21% in patients with CTS, and up to 18% were found in a retrospective study with MRI scans performed for various medical reasons . The frequency in healthy subjects is reported to be approximately 8–15% . However, no significant association between the prevalence of bifid median nerves and CTS was found in a recent study among a large population of manual workers .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This is in contrast with the most common origin of the PMA, which usually originates between the caudal angle between common interosseous artery (Rodríquez-Niedenführ et al, 1999). Walker et al (2013) reported a 3.7 % incidence of the bifid nerve, 8 % with a concomitant occurrence with a PMA. Other documented anomalies related to motor branch of the MN besides the bifid MN include ulnar and anterior take off of the motor branch, transligamentous and subligamentous course of the motor branch (Lindley & Kleneirt).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, some authors recently reported that the bifid median nerve is not an independent risk factor for development of carpal tunnel syndrome 7,9 . Meanwhile, co-existence of the bifid median nerve and persistent median artery was suggested by several authors 2,9 . Embryologically, the upper limb develops at the end of four weeks to eight weeks gestation.…”
Section: Discussionmentioning
confidence: 89%